2014
DOI: 10.4017/gt.2015.13.3.008.00
|View full text |Cite
|
Sign up to set email alerts
|

Footwear width and balance-recovery reactions: A new approach to improving lateral stability in older adults

Abstract: Background-Age-related difficulty in controlling lateral stability is of crucial importance because lateral falls increase risk of debilitating hip-fracture injury. This study examined whether a small increase in footwear sole width can improve ability of older adults to regain lateral stability subsequent to balance perturbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Furthermore, postural sway was significantly reduced at the completion of the task, indicating better balance recovery in response to the lateral instability induced by tandem walking. Several features of the prototype footwear may have been responsible for this improvement, including the supportive heel collar (by providing mechanical resistance to excessive ankle movement [ 39 ] and enhanced tactile feedback of ankle position [ 40 ]), the large surface area of the sole [ 41 , 42 ], and the textured insole providing tactile feedback relating to lateral displacement of the centre of mass [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, postural sway was significantly reduced at the completion of the task, indicating better balance recovery in response to the lateral instability induced by tandem walking. Several features of the prototype footwear may have been responsible for this improvement, including the supportive heel collar (by providing mechanical resistance to excessive ankle movement [ 39 ] and enhanced tactile feedback of ankle position [ 40 ]), the large surface area of the sole [ 41 , 42 ], and the textured insole providing tactile feedback relating to lateral displacement of the centre of mass [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cheng & Maki (2015) [86] found that a small increase in sole width improved postural stability during lateral perturbation and step reactions. Menant et al (2008a) [65] call for further studies to investigate the potential benefits of tread soled shoes for preventing slips.…”
Section: Figure 5 Pathway For Use Of Footwear Linked To Fallsmentioning
confidence: 99%
“…Greater sole/surface contact area was found to be associated with a significantly lower risk of a fall [36]. Shoes with a widened base of support improve lateral stability [43].…”
Section: Sole Width Hardness and Sole Resiliencementioning
confidence: 92%